DAMPAK SISTEMIK KORUPSI TERHADAP PEREKONOMIAN, SISTEM PENDIDIKAN, DAN PEMBAGUNAN INFRASTRUKTUR DI INDONESIA: SEBUAH ANALISIS KOMPREHENSIF - Firda Nurjihan Salsabila; Lilis Suminar; Yola Agustina; Yuni Sri Rezeki; Muhammad Fikri Ramdhani (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Corruption has been recognized as one of the main barriers to sustainable development. This research aims to analyze the systemic impact of corruption on the economy, education system, and infrastructure development in Indonesia. The method used is a literature review that examines various sources related to corruption. The results show that corruption has a negative impact on economic growth, hampers access to education, and reduces the quality of infrastructure. In addition, corruption also creates inefficiencies in budget management and undermines public trust in the government. This research emphasizes the importance of preventive measures, transparency in public financial management, and collaboration between the government, society, and the private sector to create a corruption-free system to achieve sustainable development.